1982
DOI: 10.1111/j.1570-7458.1982.tb03174.x
|View full text |Cite
|
Sign up to set email alerts
|

The Dietary Effects of Some Ecdysteroids on the Development of Housefly

Abstract: The moulting hormone activity of 13 ecdysteroids has been determined using a housefly ligature bioassay and the effects on fly development of 11 of these when incorporated !n a defined diet have been tested. The most active compounds in the moulting hormone assay were 20-hydroxyecdysone and 5,20-dihydroxyecdysone 2-(3',4'-methylenedioxy)-cinnamate while in the diet test 20-hydroxyecdysone and 5,20-dihydroxyecdysone gave 84% and 77% larval mortality, respectively at 100 ppm. 5,20-Dihydroxyecdysone 2-(3',4'methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The moulting abnormalities caused by the extracts appeared to be identical to those seen with the L. intermedius compounds 20-hydroxyecdysone, 5,20-dihydroxyecdysone, and ponasterone A. Singh et al (1982) found that when added to an amino acid diet, 20-hydroxyecdysone, 5,20-dihydroxyecdysone, and dacrysterone gave 84,77, and 52% larval mortality respectively in M. domestica at 100 ppm after 10 days. Although the serum-based assay used in this study has only a 1 -day duration, the results indicate that sensitivity of L. cuprina larvae to the phytoecdysones is similar to that of M. domestica.…”
Section: Discussionmentioning
confidence: 54%
“…The moulting abnormalities caused by the extracts appeared to be identical to those seen with the L. intermedius compounds 20-hydroxyecdysone, 5,20-dihydroxyecdysone, and ponasterone A. Singh et al (1982) found that when added to an amino acid diet, 20-hydroxyecdysone, 5,20-dihydroxyecdysone, and dacrysterone gave 84,77, and 52% larval mortality respectively in M. domestica at 100 ppm after 10 days. Although the serum-based assay used in this study has only a 1 -day duration, the results indicate that sensitivity of L. cuprina larvae to the phytoecdysones is similar to that of M. domestica.…”
Section: Discussionmentioning
confidence: 54%